Characterization and study of char performance of glass wool and rockwool hybrid fibre reinforced intumescent coatings - Amir, N. (Asian Research Publishing Network, 2016)
Intumescent fire retardant coating is widely used in the industry for protecting steel from high temperature and fire incident. The coating's application can be found in the oil and gas industries especially in the offshore structures due to its ability to withstand high temperature and severe weather. However, char strength of the existing intumescent coating can be further improved by fibre reinforcement. Previously, various researches on intumescent coating were conducted using single fibre with limited study on the hybrid fibre reinforced intumescent coating. The project examined the effects of adding hybrid fibres, exploring the mechanical and char characteristics in increasing the fire performance of the coating. The study was focused on adding glass wool fibre (G) and Rockwool fibre (R) as the hybrid reinforcement using two fibre lengths; 6 mm and 12 mm, and at 10 by weight percentage with three combinations of 3:7, 5:5 and 7:3. The investigation involved determination of potential fire resistance of the hybrid fibre reinforced intumescent coatings at various compositions and lengths of the fibres. The properties and performance of the coatings were based on the chars developed by the coatings in the furnace test. The coatings and their chars were characterized using X-Ray Fluorescence (XRF) and Scanning Electron Microscope (SEM). Finally, the chars produced were tested for strength performance test. In summary increased in the Rockwool fibre from 3 to 7 in the hybrid fibres content had produced higher char expansion (by 15.7), lower weight loss (by 22.8) as well as better char performance against loading (by 37). Â©2006-2016 Asian Research Publishing Network (ARPN).